Total and cause-specific mortality of Finnish military personnel following service in international peacekeeping operations 1990–2010: a comprehensive register-based cohort study. Issue 10 (31st October 2016) - Laukkala, T; Parkkola, K; Henriksson, M; Pirkola, S; Kaikkonen, N; Pukkala, E; Jousilahti, P
Abstract : Objectives: To estimate total and cause-specific mortality after international peacekeeping deployments among the Finnish military peacekeeping personnel in comparison to the general population of similar age and sex. Design: A register-based study of a cohort of military peacekeeping personnel in 1990–2010 followed for mortality until the end of 2013. Causes of death were obtained from the national Causes of Death Register. The standardised mortality ratio (SMR) for total and cause-specific mortality was calculated as the ratio of observed and expected number of deaths. Setting: Finland (peacekeeping operations in different countries in Africa, Asia and in an area of former Yugoslavia in Europe). Participants: 14 584 men and 418 women who had participated in international military peacekeeping operations ending between 1990 and 2010. Interventions: Participation in military peacekeeping operations. Main outcome: Total and cause-specific mortality. Results: 209 men and 3 women died after their peacekeeping service. The SMR for all-cause mortality was 0.55 (95% CI 0.48 to 0.62). For the male peacekeeping personnel, the SMR for all diseases was 0.44 (95% CI 0.35 to 0.53) and for accidental and violent deaths 0.69 (95% CI 0.57 to 0.82). The SMR for suicides was 0.71 (95% CI 0.53 to 0.92). Conclusions: Even though military peacekeeping personnel are working in unique and often stressful conditions, their mortality after their service is lower compared with the general population. Military peacekeeping personnel appear to be a selected population group with low general mortality and no excess risk of any cause of death after peacekeeping service.